11 - Alternative Modes of Financing Higher Education in Nigeria and the Implications for University Governance: 10.4314/ad.v27i1.22159 - Aina , Olabisi I. (Africa Development, 2002)
The problems of under-funding and over-reliance on government funds remain a clog in the wheel for university governance in Nigeria. The inadequate funding of the universities has had profound effects on teaching and research, while universities in Nigeria have been forced to embark on income generating projects in order to source alternative funds. Using data from a recent study, this essay explores different alternative modes of financing higher education in Nigeria, and the implications for university governance. Four Nigerian universities were surveyed, while field data were collected using the questionnaire survey method, in-depth interview, direct observation of facilities and infrastructures, and focus group discussions (FGDs). The study found that Nigerian universities are now opening up to new innovations in the area of sourcing non- governmental funds. The process has serious implications for the quality of teaching and research, while commercial ventures being generated are fraught with problems of management, including issues of accountability, profitability, and sustainability. The paper prescribes ways of overcoming some of the governance problems confronting the university system in Nigeria, as it grapples with economic realities, and the achievement of its original mission statement - teaching and research, and the building of human minds.